Reimagining Singapore in verse: A critical discourse analysis of contemporary poetry and its role in emerging national identity - Mangila, Benjamin Baguio (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
This paper critically examines how contemporary Singaporean writers use language in verse, that is poetry, to make vivid representations of Singapore as a nation and discursively construct the social notion of the country's national identity. Utilizing Wodak's (2001) Discourse-Historical framework, this paper reveals how the two authors use some common discursive strategies, mainly representational and predicational, in making explicit representations of Singapore and creating a strong sense of national identity. In their poetry, authors frequently utilize referential linguistic devices such as first personal pronouns to attach specific human traits that help personify Singapore and express an in-group identity that functions as a unifying mechanism that connects Singapore, including its people, together. Lexical repetitions and rhetorical figures are also used to convey more emphasis and reveal the authors' intended meanings or messages. The authors employ various descriptive words to create better and more accurate imageries of Singapore as a varied community and as a nation. Furthermore, the authors' discursive techniques perform both the "constructing" and "preserving" macro-functions by discursively constructing Singapore's national identity as well as making an urgent call to all Singaporeans to safeguard their collective identity.